Persepsi Risiko Covid-19 terhadap Intensi Berwisata di Jabodetabek - Fredy Utama; Doddy Setiawan (Jurnal Bisnis dan Manajemen, 2020)
Since the Covid-19 pandemic has been declared as a global pandemic, tourism was the most affected sector by pandemic Covid-19. For the tourism industry, there are direct consequences for the national and local restrictions that have a direct impact on people's lives to minimize the spread of the virus. There are human mobility and the possibility of direct physical contact between individuals. Several things that are considered by tourists in making travel decisions, including the risk perception and their travelling’s safety to a destination. There are several risk perceptions, namely the financial risk perception, time risk, social-psychological risk and health risk. Hypothesis using SEM AMOS to majority 16-25 years old respondents, found no direct influence between perceived risk and intention to travel. The results showed that an increase in risk perception did not affect a decrease in travel intention. Among the 4 variables tested, perceptions of financial risk have the greatest influence, followed by perceptions of health risk, social-psychological risk and time risk.